Financial Development and Income Inequality in Bangladesh: Empirical Evidence from Vector Auto-Regression (VAR) Model - SIDDIQUE, Md Abu Bakkar (South Asian Journal of Social Sciences and Humanities, 2024)
This study investigates the effect of financial development on inequality in Bangladesh. We run a vector autoregressive (VAR) model for the economy of Bangladesh from 1980 to 2020. Using the impulse response functions (IRFs), we find that the disposable income and market income Gini coefficients respond positively to private credit. It suggests that financial development contributes to raising inequality in Bangladesh. We also find that growth has an adverse impact on inequality whereas income inequality has a positive effect on economic growth. However, economic growth has a greater and more pronounced negative effect on inequality than inequality itself, even though these two variables exhibit opposite interaction responses. It indicates that growth lowers inequality in Bangladesh.The forecast error variance decomposition function shows that private credit can explain the variations of disposable income Gini by 8.65 percent; on the other hand, disposable income Gini can explain the variation of private credit by 8.90 percent.